If it's not what You are looking for type in the equation solver your own equation and let us solve it.
20+-26=m
We move all terms to the left:
20+-26-(m)=0
We add all the numbers together, and all the variables
-m=0
m=0/-1
m=0
| g/4-(-6)=9.77 | | -5-4k=-25 | | -8(1-5x)+5(-8x-2)=-4x-8x | | -5-4k=-26 | | -6+6(-10p)=10(-8p+5) | | u-2(7)+40=7+2u | | (7p+13)+2p=4+18 | | 3e+6=2(6) | | 4(9k+10)=-4(-8k+8) | | z^4=-625 | | (7p+13)+4=2p+18 | | -12(1-2m)+5(6-3m)=3m+30 | | (x+0.5)+4=12 | | (7p+13)=2p | | -5x+14=-5 | | 4(11v+12)=6(12-5v)-8v | | 6x+4x+12=360 | | 7u+8=9u | | 4v-11+7v-2=9(v+7)-11(v+1) | | 4t=2t+40 | | 70x^2-64x-3=0 | | 4x13=27 | | (4x-35)=(2x-17) | | 6 | | 2+4(2x-1=6.25x+26 | | 2x+22.4=90 | | 5y+5y=7 | | 48*56=3*7*(2^c) | | -8m+5(-3+2m)-3=2m-20 | | 3(m+2)=21(8m+24) | | 12b+15+17b=46 | | 48*56=3*7*2^c |